Purinergic system dysfunctions in subjects with bipolar disorder: A comparative cross-sectional study - Bartoli, Francesco; Crocamo, Cristina; Dakanalis, Antonios; Brosio, Enrico; Miotto, Alessio; Capuzzi, Enrico; Clerici, Massimo; Carrà, Giuseppe (Comprehensive psychiatry, 2017)
Subjects with bipolar mania may have increased uric acid levels, based on a purinergic system dysfunction with reduced neurotransmission of adenosine. We investigated whether there were differences in uric acid levels between individuals with bipolar disorder (in manic or depressive phases) and those with major depressive disorder. We conducted a cross-sectional study recruiting 128 subjects with bipolar disorder and 118 with major depressive disorder, admitted to a psychiatric inpatient unit. Standard demographic and clinical information were retrieved from electronic charts and relevant clinical records. Fasting serum values of uric acid, as well as metabolic (total cholesterol, triglycerides, and glycaemia), oxidative stress (albumin, bilirubin), and kidney function (creatinine), parameters, were collected. Subjects with bipolar mania (5.27±1.63mg/dL), but not those with bipolar depression (4.89±1.94mg/dL), had higher levels of serum uric acid (p<0.05), as compared with individuals with major depressive disorder (4.59±1.62mg/dL). Relevant linear regression analyses, controlling for metabolic profile, oxidative stress markers, kidney function, and comorbid alcohol use disorder, showed a significant association between bipolar mania (p<0.01) and increased uric acid. Findings of this study add evidence to the role of uric acid as state, rather than trait, marker in bipolar disorders. Explored, relevant, confounders do not seem to influence these results. The current study supports the hypothesis of a purinergic system dysfunction associated with manic phases of bipolar disorder.